La Filosofía del derecho de Hegel: ¿Política, no Metafísica? - Giusti, Miguel (Revista Eletrônica Estudos Hegelianos, 2021)
Perhaps unconsciously emulating the intention of John Rawls to turn liberalism into a purely political theory, without presuppositions or metaphysical pretensions, some contemporary authors propose to update the central approaches of Hegel's Philosophy of Right, but also to dispense it with its dependence on his Science of Logic. We will analyze whether this claim is possible, and for this we will focus especially on the methodological strategy used by Axel Honneth in his various works on the matter. Even recognizing the relative plausibility that such an undertaking can have, we will argue, however, not only that it is not possible to dispense with those metaphysical presuppositions, but that, well understood, they actually constitute the greatest richness of the most relevant ideas of the Philosophy of Right. We will make a differentiation between immediate, mediate and hermeneutical presuppositions, and this should show us the different levels of dependence between the two mentioned works of Hegel.